INFLUENCE OF REGIONAL TAXES, BALANCING FUNDS, AND REGIONAL RETRIBUTION ON CAPITAL EXPENDITURE IN REGENCY/CITY GOVERNMENTS IN CENTRAL JAVA PROVINCE YEAR 2018-2021 - Budiyono, Budiyono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Study This aiming For knowing : 1) Influence Regional Taxes on Capital Expenditure on Government Regency and Cities in the Province Central Java 2018-2021 ; 2) Influence of Balancing Funds to Capital Expenditure on Government Regency and Cities in the Province Central Java 2018-2021 ; 3) Influence Regional Retributions on Capital Expenditure on Government Regency and Cities in the Province Central Java 2018-2021 . Object on study This is government regency And cities in the Province Central Java has 35 districts And city . Data retrieval comes from from Report Realization of the 2018-2021 APBD . Engineering data collection using method documentation . Technique data analysis using test assumption classic that is test normality , test multicollinearity , test heteroscedasticity , and test autocorrelation . Testing hypothesis in study This use analysis multiple linear regression , F test , t test , and test coefficient determination (R 2 ). Results study show that : 1) Regional taxes have an impact significant to Capital Expenditure on Government Regency and Cities in the Province Central Java 2018-2021 ; 2) Balancing Funds influential significant to Capital Expenditure on Government Regency and Cities in the Province Central Java 2018-2021 ; 3) Regional Retribution has an impact significant to Capital Expenditure on Government Regency and Cities in the Province Central Java 2018-2021 .